2020
DOI: 10.3390/cancers12113146
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Landscape of Papillary Thyroid Carcinoma and Nuclear Architecture: An Overview Comparing Pediatric and Adult Populations

Abstract: Thyroid cancer is a rare malignancy in the pediatric population that is highly associated with disease aggressiveness and advanced disease stages when compared to adult population. The biological and molecular features underlying pediatric and adult thyroid cancer pathogenesis could be responsible for differences in the clinical presentation and prognosis. Despite this, the clinical assessment and treatments used in pediatric thyroid cancer are the same as those implemented for adults and specific personalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 220 publications
(324 reference statements)
5
55
0
10
Order By: Relevance
“…For adults, the most common genetic changes are B-Raf proto-oncogene (BRAF V600E) and RAS (a family of small membrane GTPases) point mutations and rearranged in transformation/papillary thyroid carcinomas (RET/PTC) fusions. Human telomerase reverse transcriptase (HTERT) promoter mutations have been observed in adult papillary thyroid cancer (PTCs) and are associated with a more aggressive phenotype [ 11 , 12 , 13 , 14 , 15 , 16 ]. Gene mutations and RET/PTC, ETV6-NTRK3, and BRAF fusions (AGK-BRAF and AKAP9-BRAF) are more common in the pediatric population, especially up to the age of 10 years.…”
Section: Introductionmentioning
confidence: 99%
“…For adults, the most common genetic changes are B-Raf proto-oncogene (BRAF V600E) and RAS (a family of small membrane GTPases) point mutations and rearranged in transformation/papillary thyroid carcinomas (RET/PTC) fusions. Human telomerase reverse transcriptase (HTERT) promoter mutations have been observed in adult papillary thyroid cancer (PTCs) and are associated with a more aggressive phenotype [ 11 , 12 , 13 , 14 , 15 , 16 ]. Gene mutations and RET/PTC, ETV6-NTRK3, and BRAF fusions (AGK-BRAF and AKAP9-BRAF) are more common in the pediatric population, especially up to the age of 10 years.…”
Section: Introductionmentioning
confidence: 99%
“…Specific telomere profiles are associated with disease stability vs. progression [ 18 , 21 , 22 , 23 , 24 , 25 ]. Critically short telomeres, telomere dysfunction, and fusions have all been correlated with disease progression [ 18 , 25 , 27 , 28 , 29 ]. Therefore, telomere profiling may represent both a clinically useful prognostic tool and a potential guide for therapeutic intervention [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the genetic features of pediatric patients was different from adults [30][31][32] . The BRAF V600E mutation occurred in 27-83% of adult PTC cases, and was associated with the aggressive tumor features and poor outcome [32,33] . However, the frequency of BRAF V600E was about 19% in pediatric patients [34] , which was signi cantly lower.…”
Section: Discussionmentioning
confidence: 99%